2021
DOI: 10.4314/ovj.v11i1.3
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of osteosarcoma after tibial fracture repair in a dog

Abstract: Background: There are few detailed reports on implant-associated sarcoma in dogs; however, loose implants, metal type, and infection have not been shown as specific risk factors for this condition. Case Description: A 14-year-old spayed female Labrador retriever was referred to our hospital with a main complaint of chronic right hind lameness after previous tibial fracture repair. On radiographs, rupture of the bone plate and screws with swelling of the surrounding soft tissue was observed, and osteosarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…reports describe an OS developing 6 years after a TPLO procedure 26 ; a Cane Corso is reported to have OS arising 6 years after a tibial tuberosity advancement 31 ; and in a Labrador Retriever 12 years after tibial fracture repair. 32 This latter dog died 1 month following amputation of the tumourcontaining limb. 32 Fracture-induced or metallic implantassociated OS specifically developing around the TPLO plate has a median occurrence of 2 to 4 years following the procedure.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…reports describe an OS developing 6 years after a TPLO procedure 26 ; a Cane Corso is reported to have OS arising 6 years after a tibial tuberosity advancement 31 ; and in a Labrador Retriever 12 years after tibial fracture repair. 32 This latter dog died 1 month following amputation of the tumourcontaining limb. 32 Fracture-induced or metallic implantassociated OS specifically developing around the TPLO plate has a median occurrence of 2 to 4 years following the procedure.…”
Section: Discussionmentioning
confidence: 97%
“…32 This latter dog died 1 month following amputation of the tumourcontaining limb. 32 Fracture-induced or metallic implantassociated OS specifically developing around the TPLO plate has a median occurrence of 2 to 4 years following the procedure. 30 Factors possibly promoting the development of fracture-related sarcomas include patient sensitivity to the implant, implant corrosion, instability of the fracture or inappropriate bone healing.…”
Section: Discussionmentioning
confidence: 97%
“…True incidence of STS in dogs is unknown but it has been previously suggested that these tumours account for 9%–15% of all cutaneous and subcutaneous canine tumours 1 . The underlying causes for sarcomas are varied and multifactorial 2–28 . In dogs, STS have been associated with radiation, trauma, chronic inflammation and parasitic infection 2–6 .…”
Section: Introductionmentioning
confidence: 99%